Analysis of Information Management System Utilization at Pelengkap Medical Center Hospital, Jombang, East Java - Adiansa, Rendi; Tamtomo, Didik Gunawan; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Hospital Management Information System (SIMRS) is an information technology system that integrates the entire flow of hospital services in the form of a network of coordination, reporting, and administrative procedures to obtain precise and accurate information. The successful implementation of SIMRS depends on the use of the system by staff working in health care facilities. The model used in analyzing the use of SIMRS is the Technology Acceptance Model (TAM). The purpose of this study was to determine the effect of the TAM construct variable on the use of SIMRS.Subjects and Method: This was an analytical observational study with a cross-sectional design. The study was conducted in Pelengkap Medical Center Hospital, Jombang, East Java, in April 2022. A sample of 73 staff was selected by random sampling. The sampled staff are active users of SIMRS for at least 1 year. The dependent variable was the use of SIMRS. The independent variables observed were profession and training education. The data were collected by questionnaire and analzed by path analysis.Results: MIS utilization was directly affected by positive attitude (b= 3.12; 95% CI= 1.67 to 4.58; p<0.001) and perceived ease of use (b= 2.07; 95% CI= 0.63 to 3.50; p= 0.005). It was indirectly affected by education/ trining, profession, and perceived benefit.Conclusion: MIS utilization is directly affected by positive attitude and perceived ease of use. It is indirectly affected by education/ trining, profession, and perceived benefit.Keywords: SIMRS, Technology Acceptance ModelCorrespondence:Rendi Adiansa. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: adiansarendi@gmail.com. Mobile : 08816008735Journal of Health Policy and Management, (2022), 07(02): 166-175https://doi.org/10.26911/thejhpm.2022.07.02.08